2021
DOI: 10.1177/00144029211062595
|View full text |Cite
|
Sign up to set email alerts
|

Are Paraprofessionals Being Hired to Replace Special Educators? A Study of Paraprofessional Employment

Abstract: Special education teacher employment began to decline in 2006, concurrent with increased paraprofessional employment. At the same time, the prevalence of students with disabilities in several categories changed substantially, and the proportion of students being served in general education settings increased as well. The purpose of this study was to determine whether the decline in special education teacher employment was related to increased paraprofessional employment, and if the increase in paraprofessional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…From the few that could be found, trends presented mixed findings. Fisher et al (2021) found that more paraprofessionals are being hired to replace SnE, specifically in the context of students with autism spectrum disorders. It was also found while paraprofessionals lack training in curricular and instructional decisions, estimates of the proportion of paraprofessionals that makes curricular decisions ranged up to 70% (Fisher et al, 2021).…”
Section: Context Of Professional Distinctionmentioning
confidence: 99%
See 4 more Smart Citations
“…From the few that could be found, trends presented mixed findings. Fisher et al (2021) found that more paraprofessionals are being hired to replace SnE, specifically in the context of students with autism spectrum disorders. It was also found while paraprofessionals lack training in curricular and instructional decisions, estimates of the proportion of paraprofessionals that makes curricular decisions ranged up to 70% (Fisher et al, 2021).…”
Section: Context Of Professional Distinctionmentioning
confidence: 99%
“…Fisher et al (2021) found that more paraprofessionals are being hired to replace SnE, specifically in the context of students with autism spectrum disorders. It was also found while paraprofessionals lack training in curricular and instructional decisions, estimates of the proportion of paraprofessionals that makes curricular decisions ranged up to 70% (Fisher et al, 2021). Sindelar, Brownell and Billingsley (2010) found that almost half of the first-year teachers that enter special needs schools do not meet the basic requirements for teaching.…”
Section: Context Of Professional Distinctionmentioning
confidence: 99%
See 3 more Smart Citations